PENDEKATAN KRITIS, ETIS, DAN ISLAMI DALAM MANAJEMEN PENDIDIKAN ISLAM DI SMP IT ABU BAKAR SIDDIQ: PENDEKATAN KRITIS, ETIS, DAN ISLAMI DALAM MANAJEMEN PENDIDIKAN ISLAM DI SMP IT ABU BAKAR SIDDIQ (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic educational management demands an integration of modern management principles and Islamic values. In the context of SMPIT Abu Bakar Siddiq, critical, ethical, and Islamic approaches are essential foundations for creating educational governance that is just, imbued with integrity, and spiritually oriented. This research employed a descriptive qualitative method with a case study approach. The results indicate that the critical approach is implemented through a reflective and participatory culture; the ethical approach through honesty and responsibility-based leadership; and the Islamic approach through internalizing the values ​​of monotheism and trustworthiness. These three approaches form a synergy of morally and spiritually oriented management.